MIDDELFART SPAREKASSE : Architecture and the Workplace - Bundegaard, Christian, 1961- 632193 (Berlin : Bilingual, 2010)
Middelfart Savings Bank is far from just a bank and thus its new head office is not just a traditional office building. It is, in fact, a realization of the bank's ambition to be amongst the best workplaces in Denmark and-- at the same time --to act as a social agent in the local community. 3XN interpreted these ambitions into a tactile design, understanding architecture as a comprehensive framework for social life. Six months after its inauguration, the building has been nominated for several international architecture awards and has been referred to as Denmark's best office building by a leading Danish architecture critic.